(untitled) (AYUSHDHARA, 2024)
Traumatic tympanic membrane perforations are common in Otolaryngological practice. These perforations can be due to direct penetrating trauma, infections or due to eustachian tube disorders. These perforations can lead to reversible high frequency deafness, tinnitus and vertigo. Small perforations heal spontaneously within three months after the injury while large perforations are treated with myringoplasty. This is a case report of 35year old female patient who presented to Shalakya OPD with complaints of sudden onset of earache and reduced clarity of hearing in left ear, since 7 days. The tympanic membrane was ruptured. While compairing the size of perforation relative to circumference of the tympamic membrane, it was observed to be a large sized perforation affecting 50% of tympamic membrane. Large sized perforations are usually considered non healing as it exert influence on the malleus and umbo at tympanic membrane insertion and would interrupt the sound conducting mechanism. She was managed conservatively with Ayurveda treatment. Karnalepa applied over the pre auricular and mastoid region makes the healing fast and effective. Karnapichu, the modified form of karnapoorana provides a much larger skin contact time with controlled release of drugs.The case report shows the effect of local and systemic medication in the form of Murivenna karnapichu. The healing of tympanic membrane occurred within one month of follow up.